Design of an Experimental Facility for Thermographic Analysis of Photovoltaic Installations - Ventsislav Keseev; Boris Evstatiev; Nicolay Mihailov; Tsvetelina Mladenova; Vladislav Hinkov (Engineering Proceedings, 2024)
Regular inspections of photovoltaic (PV) installations are an important procedure for optimizing their efficiency and prolonging their life expectancies; however, this might be a costly activity. One of the alternatives is visual monitoring using cameras with different spectra. This study presents the design and development of an experimental facility to conduct a wide range of thermographic studies. Initially, the common non-invasive inspection technologies are reviewed; then, an appropriate one is chosen according to the requirements of the lab. Next, the designed facility is analyzed in terms of resolution and accuracy, and the pixel count per solar cell is obtained for the different areas of the installation site. This study also analyzes the possible research activities that could be implemented within the created facility. They have been summarized in four categories: the identification of the type of soiling over a PV surface; the modeling of a string efficiency decrease as a function of partial shading/soiling of its surface; the investigation of the influence of distance on the accuracy and uncertainty of the performed IR measurements; and the continuous long-term monitoring of the PV installation. Examples of the above categories are also shown, which demonstrate the identification of typical urban PV exploitation situations with the infrared camera.